EMPLOYMENT LEGAL ENTITY OF THE EMPLOYER AS A PREREQUISITE OF LIABILITY OF THE EMPLOYER FOR VIOLATION OF LEGISLATION ON LABOR - Kliets, Tetiana (Global Prosperity, 2021)
The article analyzes the essence of the labour legal personality of the employer as a prerequisite for the employer’s liability for violation of labour legislation. The author presented scientific views on the definition of legal personality and determined the content of the employer’s employment status. By assessing the place of tort in it, the author proved that its legal significance is revealed by the fact that after acquiring the appropriate status, a person receives or is endowed by law with a set of rights and responsibilities that determine the behaviour of this person as an employer. Thus, tort always involves implementing a voluntary act, the result of which is the actual acquisition of legal liability. Delinquency is a set of legally embodied (and mandatory) indicators and characteristics of a person, which together indicate the ability of such a person to be responsible. The employer’s status determines tort, and therefore at the level of contractual relations, it is detailed through a set of reasons for which a person acquires responsibility. It is determined that the responsibility for violation of labour legislation, as an element of the employer’s legal personality and legal status, has an individual expression. That is, a natural person is held liable: Private individual – as a natural person with special status; the head or authorized person of the legal entity – as a person who formally acts as a party to the employment and/or a collective agreement; a legal entity of private and/or public law in some cases where the liability does not require individualization. Considering the general nature of legal liability and the peculiarities of its manifestation in violation of labour legislation, the author found that the individualization requires criminal and administrative liability, as well as disciplinary, but within the legal entity of the employer. Promising areas of further research are the development of the paradigm of labour legal personality of the employer, as a basis for developing an independent institution of penalties for violations of labour legislation and the study of the variety of forms of liability of the employer for violations of labour legislation.